The Next Innocence Project: Shaken Baby Syndrome and the Criminal Courts - Deborah Tuerkheimer (Washington University Law Review, 2009)
Every year in this country, hundreds of people are convicted of having shaken a baby, most often to death. In a prosecution paradigm without precedent, expert medical testimony is used to establish that a crime occurred, that the defendant caused the infant’s death by shaking, and that the shaking was sufficiently forceful to constitute depraved indifference to human life. Shaken Baby Syndrome (SBS) is, in essence, a medical diagnosis of murder, one based solely on the presence of a diagnostic triad: retinal bleeding, bleeding in the protective layer of the brain, and brain swelling. New scientific research has cast doubt on the forensic significance of this triad, thereby undermining the foundations of thousands of SBS convictions. Outside the United States, this scientific evolution has prompted systemic reevaluations of the prosecutorial paradigm. In contrast, our criminal justice system has failed to absorb the latest scientific knowledge. This is beginning to change, yet the response has been halting and inconsistent. To this day, triad-based convictions continue to be affirmed, and new prosecutions commenced, as a matter of course. This Article identifies a criminal justice crisis and begins a conversation about its proper resolution. The conceptual implications of the inquiry—for scientific engagement in law’s shadow, for future systemic reform, and for our understanding of innocence in a post-DNA world—should assist in the task of righting past wrongs and averting further injustice.
Keywords: Shaken baby syndrome; Criminal law; Expert evidence; Scientific evidence (Law); Criminal intent; Causation (Criminal Law)